Answer to Question #215485 in Differential Equations for Krk

Question #215485

(D2-2D+3) y=x2

1
Expert's answer
2021-07-11T17:21:52-0400

Let us solve the differential equation "(D^2-2D+3) y=x^2." Its characteristic equation "k^2-2k+3=0" is equivalent to "(k-1)^2=-2," and hence has the roots "k_1=1+i\\sqrt{2}" and "k_2=1-i\\sqrt{2}." Therefore, the general solution is of the form "y=e^x(C_1\\cos(\\sqrt{2}x)+C_2\\sin(\\sqrt{2}x))+y_p," where "y_p=ax^2+bx+c." It follows that "y_p'=2ax+b,\\ y_p''=2a." We have the equation "2a-2(2ax+b)+3(ax^2+bx+c)=x^2," which is equivalent to "3ax^2+(-4a+3b)x+(-2b+3c)=x^2." It follows that "3a=1,\\ -4a+3b=0,\\ -2b+3c=0." Then "a=\\frac{1}{3},\\ b=\\frac{4}{9},\\ c=\\frac{8}{27}." We conclude that the general solution is the following:

"y=e^x(C_1\\cos(\\sqrt{2}x)+C_2\\sin(\\sqrt{2}x))+\\frac{1}{3}x^2+\\frac{4}{9}x+\\frac{8}{27}."



Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog